MEANS OF TEACHING STUDENTS TO LOVE BOOKS - Olimova Dilshodaxon Baxtiyorjon qizi; Isakov Zakirjon Soliyevich (International Engineering Journal For Research & Development, 2021)
In order to ensure a harmonious future for the younger generation, the article discusses the role of books in the upbringing of children and their importance in human life in general, and the importance of this in the primary education system.